No interest, no time! Gendered constraints to museum visits in Flanders. Issue 2 (4th May 2019) - Mullens, Francisca; Glorieux, Ignace
Abstract : This paper investigates why non-attendees of museums in Flanders (Belgium) do not visit and how these reasons for not attending are related to gender. The hierarchical constraints framework is applied to non-attendees using the 2014 Participation Survey ( N  = 2707). Both interested and non-interested non-attendees are included in the analyses. Findings reveal that interest constraints are the greatest barrier for museum visits for both women and men. However, men do report this type of constraint more than women. Women, on the other hand, report more interpersonal and structural constraints. Older women seem doubly disadvantaged regarding interpersonal constraints, and women with a lower subjective income are doubly disadvantaged for both interpersonal and structural constraints. This paper explains discrepancies in the experiences of constraints between different groups by the hierarchy of social privilege, referring to the role of socialization and culture in influencing people's preferences. Evaluating the constraint model in research regarding cultural participation, the paper proposes a clarification based on Parsons' action theory framework.